2018
DOI: 10.1002/jssc.201700777
|View full text |Cite
|
Sign up to set email alerts
|

Rapid characterization of the absorbed chemical constituents of Tangzhiqing formula following oral administration using UHPLC–Q‐TOF‐MS

Abstract: Tangzhiqing formula, a Chinese herbal formula, is used for the treatment of type II diabetes and prediabetes. Although its effectiveness has been certified by clinical use, its absorbed chemical constituents are not comprehensively represented. Thence, in order to reveal potential bioactive components and metabolism of Tangzhiqing formula, an ultra-high performance liquid chromatography with quadrupole time-of-flight mass spectrometry method was developed. A total of 86 absorbed components, including 38 protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Diterpenoid quinines are the major components in S. miltiorrhiza. In addition, more sensitive fragmentation information was observed in the positive ion mode, as they are easy to capture a proton to form the molecular ions 14 . The neutral loss of H 2 O and CO was supposed to be generated from the cleavage of the carbonyl linkage on the C ring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diterpenoid quinines are the major components in S. miltiorrhiza. In addition, more sensitive fragmentation information was observed in the positive ion mode, as they are easy to capture a proton to form the molecular ions 14 . The neutral loss of H 2 O and CO was supposed to be generated from the cleavage of the carbonyl linkage on the C ring.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, more sensitive fragmentation information was observed in the positive ion mode, as they are easy to capture a proton to form the molecular ions. 14…”
Section: Diterpenoid Quinonesmentioning
confidence: 99%
“…Based on chemical and metabolic analyses of TZQ disposition, 86 components and 48 metabolites were detected in rat plasma, urine, and feces. The primary components absorbed are flavonoids and alkaloids, while the primary metabolites are glucuronides and sulfates ( Wu et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro experiment demonstrated that 2,3,4,6-tetra-O-galloyl-D-glucose, 1,2,3,4-tetra-O-galloyl-D-glucose, 1,2,3,4,6-penta-O-galloyl-d-glucose, quercetin-3-O-β-D-glucuronide and quercetin-3-O-β-D-glucoside were the primary biological active components of SYT due to the inhibitory effects on maltase, invertase, and lipase ( Tao et al, 2013 ). After oral administration of SYT, 86 components were identified in rat plasma, urine, and feces, including alkaloids, flavonoids, phenolic acid, diterpenoid quinones, monoterpenoids, and metabolites of glucuronidation and sulfation, which were found to be absorbed components ( Wu et al, 2018 ). Nuciferine and paeoniflorin were suggested as the quality markers of SYT ( Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%